Digital Transformation of Public Procurement as an Opportunity for the Economy - Nina Pekolj; Katja Hodošček; Lara Valjavec; Petra Ferk (LeXonomica, 2019)
In this paper, the authors investigate the impact of digitalisation of public procurement on the prospects of improving public procurement and thus enhancing the economies of the Member States and, consequently, the EU. Electronic procurement should not be perceived as a burden but rather an opportunity for the economy since it can provide solutions to many of the challenges we are facing in the public procurement—high costs of participation in public procurement procedures, lack of competition, accelerating opportunities for the economy, bid rigging, artificial splitting of contracts, and low statistics in cross-border and joint procurement. Therefore, the economy and the governments should fully exploit the advantages it offers. However, this is not going to be achieved by merely adopting the public procurement legislative rules (in 2014, the latter introduced mandatory electronic procurement), but rather by changing the perspective/relationship towards eProcurement and focusing more on the development of skills and professionalisation to fully exploit the potential of digitalisation in public procurement.